2009
DOI: 10.1007/s00404-009-1300-0
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparison of vaginal stump suturing techniques during total laparoscopic hysterectomy

Abstract: The two-layer running suture technique was safe and effective for vaginal cuff suture during TLH, but there was no statistically significant advantage over the widely used figure-of-eight suture method. Diabetes, cigarette smoking and pelvic adhesions produced statistically significant increased risks of complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 20 publications
0
35
1
1
Order By: Relevance
“…Uccella et al reported a threefold increased incidence of VCD associated with laparoscopic single-layer interrupted sutures [24]. However, Jeung et al reported no differences between laparoscopically interrupted and running sutures in their prospective study involving benign gynecologic patients who were treated with a hysterectomy [25]. Regrettably, in the present study, we did not compare the efficacy of running and interrupted sutures.…”
Section: Discussioncontrasting
confidence: 46%
“…Uccella et al reported a threefold increased incidence of VCD associated with laparoscopic single-layer interrupted sutures [24]. However, Jeung et al reported no differences between laparoscopically interrupted and running sutures in their prospective study involving benign gynecologic patients who were treated with a hysterectomy [25]. Regrettably, in the present study, we did not compare the efficacy of running and interrupted sutures.…”
Section: Discussioncontrasting
confidence: 46%
“…This is attributed to the high frequency surgical detachment of the uterus from the vagina, whereby the endoscopic suturing technique is also discussed. A randomized study of vaginal stump suturing techniques comparing vaginal and laparoscopic approaches by an experienced surgeon did not yield any differences [37].…”
Section: Total Laparoscopic Hysterectomy (Tlh)mentioning
confidence: 89%
“…[33] Moreover, previous studies have demonstrated that 2-layer suture was associated with low incidence of vaginal cuff dehiscence. [3435] In our cohort, vaginal cuff closure was performed using the 2-layer suture method. It may be one of the reasons why the incidence of vaginal cuff dehiscence in our report was low.…”
Section: Discussionmentioning
confidence: 99%